Preparation-and Spectroscopic Characterization of Transition Metal Complexes with Schiff base 2-[1-(1H-indol-3-yl)ethylimino) methyl]naphthalene-1-ol (Baghdad Science Journal, 2022)
The ligand 2-[1-(1H-indol-3-yl)ethylimino) methyl]naphthalene-1-ol, derived from 1-hydroxy-2-naphthaldehyde and 2-(1H-indol-3-yl)ethylamine, was used to produce a new sequence of metal ions complexes. Thus ligand reactions with NiCl2.6H2O, PdCl2, FeCl3.6H2O and H2PtCl6.6H2O were sequentially made to collect mono-nuclear Ni(II), Pd(II), Fe (III), and Pt(IV). (IR or FTIR), Ultraviolet Reflective (UV–visible), Mass Spectra analysis, Bohr-magnetic (B.M.), metal content, chloride content and molar conductivity have been the defining features of the composites. The Fe(III) and Pt(IV) complexes have octahedral geometries, while the Ni(II) complex has tetrahedral geometry and the Pd (II) complex has square planer geometry, according to these findings.